Oxone promoted dehydrogenative Povarov cyclization of N-aryl glycine derivatives: an approach towards quinoline fused lactones and lactams - More, Devidas A.; Shinde, Ganesh H.; Shaikh, Aslam C.; Muthukrishnan, M. (RSC Advances, 2019)
Oxone promoted intramolecular dehydrogenative imino Diels-Alder reaction (Povarov cyclization) of alkyne tethered N-aryl glycine esters and amides has been explored, thus affording biologically significant quinoline fused lactones and lactams. The reaction is simple, scalable, and high yielding (up to 88%). The method was further extended to prepare biologically important luotonin-A analogues and the quinoline core of uncialamycin.